"A SERIOUSNESS THAT FAILS": RECONSIDERING SYMBOLISM IN OSCAR WILDE'S SALOMÉ. Issue 1 (13th February 2017) - Im, Yeeyon
Abstract : Writing as recently as 2011, Michael Bennett asks if Salomé is an anomaly in the oeuvre of Oscar Wilde (viii). Read against his witty societal comedies of manners, it certainly appears to be one. Salomé has been regarded as a fine example of symbolist drama in the history of British theatre, and few critics would dispute its "seriousness" as such. Its growing significance in recent discourses of gender and sexuality also adds seriousness to the play. Although Feminist and gender critics show little qualms about dubbing the play as symbolist, the final tableau of a young girl kissing the mouth of the severed head seems to me at odds with symbolism, whether Salomé is seen as an archetypal femme fatale, a queer man in disguise, or a New Woman as critics argue. Symbolism in Wilde's Salomé is widely different from other specimens of the genre such as Yeats's The Countess Cathleen, for instance, which directly deals with a spiritual issue of the salvation of soul. Salomé also lacks the fatalistic sense of doom that dominates Maeterlinck's Princess Maleine, with which it is often compared. Wilde's wayward heroine is not a victim of the invisible forces in the same way Maeterlinck's characters are. Wilde's Salomé is "monstrous, " as Herod says: she seems to commit "a crime against some unknown God" ( Complete Works 604). How can we reconcile her cruel passion of carnal desire with the supposed spirituality of the symbolist tradition? Also problematic in a symbolist reading of the play is the presence of the comic and the parodic, as pointed out by many critics. Is Wilde's Salomé an authentic symbolist drama?